Upaya Penanggulangan dan Pertanggungjawaban terhadap Pelaku Tindak Pidana Pedofilia dalam Perspektif Keadilan di Desa Oesena, Kecamatan Amarasi, Kabupaten Kupang - Eleonoris Agusto Parera; Reny Rebeka Masu; Rudepel Petrus Leo (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Tackling pedophilia crimes often faces serious obstacles, especially when the perpetrator has a high social status or strong influence in society. This condition often hampers the law enforcement process, because it is difficult to hold the perpetrator criminally accountable fairly. This research is an empirical legal research by conducting interviews and observing examination files and related documents.The results of this study indicate that: (1) efforts to combat pedophilia crimes that occurred in Oesena Village have not been optimal due to weak coordination between parties. The police are overwhelmed in handling similar cases, while legal aid institutions can only provide assistance without full legal authority, even though they try through social media. As a result, the victims have not received legal justice. (2) the accountability of perpetrators of pedophilia crimes seen from the aspect of justice has not been fulfilled, both legally and socially. Legally, the perpetrators have not received appropriate punishment. This shows that the perpetrators have not been truly held accountable for their actions fairly.